Dapagliflozin improves cardiac function and reduces adverse events in myocardial infarction: a meta-analysis in diabetic and non-diabetic populations - Li, Shuang; Wang, Longlong; Wang, Peng; Xu, Xiaohui; Guo, Yanhua (Frontiers in Endocrinology, 2025)
BackgroundMyocardial infarction (MI) remains a leading cause of morbidity and mortality worldwide, frequently driven by acute coronary occlusion resulting from atherosclerosis and arrhythmias. Type 2 diabetes mellitus (T2DM) is a major risk factor for atherosclerotic progression and is associated with worsened cardiovascular outcomes in post-MI patients. Dapagliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, has emerged as a novel antidiabetic agent with additional cardiovascular benefits. Increasing evidence suggests its potential utility in post-MI care, particularly in patients with coexisting T2DM.ObjectiveThis study aims to systematically evaluate the clinical efficacy of dapagliflozin in improving cardiac function and reducing adverse cardiovascular events in post- MI patients with and without diabetes.MethodsA systematic search of PubMed, Embase, Web of Science, Cochrane Library, CNKI, and WanFang databases identified relevant clinical studies up to May 22, 2024. Eligible randomized controlled trials (RCTs) and retrospective cohort studies were analyzed using Review Manager 5.3.Results19 studies (12 RCTs and 7 cohort studies) with 7,128 patients were included. Meta-analysis showed dapagliflozin significantly reduced key cardiac biomarkers and structural parameters, including NT-proBNP (MD = -62.06, 95% CI [-94.59, -29.53], P = 0.0002), LVEDD (MD = -2.58, 95% CI [-3.64, -1.52], P < 0.00001), and LVESD (MD = -2.32, 95% CI [-2.99, -1.66], P < 0.00001), while enhancing LVEF (MD = 3.88, 95% CI [2.24, 5.52], P < 0.00001). It also reduced major adverse cardiovascular events (RR = 0.33, 95% CI [0.18, 0.60], P < 0.05), and heart failure-related rehospitalization (RR = 0.53, 95% CI [0.30, 0.91], P < 0.05). Subgroup analysis revealed consistent cardioprotective benefits in both diabetic and non-diabetic populations.ConclusionDapagliflozin significantly enhances cardiac function and reduces adverse cardiovascular events in post-MI patients, independent of diabetes status. These findings support the integration of dapagliflozin into post-MI management strategies. Further large-scale, long-term clinical trials are needed to assess its impact on recurrent MI and long-term survival outcomes.